Keys to Galatians collected essays - Murphy-O'Connor, J. 1935-2013 (Collegeville, Minn Liturgical Press, 2012)
Missions in Galatia, Macedonia, and Achaia before the Jerusalem Conference -- Paul in Arabia (Gal 1:17) -- The names for Jerusalem in Galatians (1:17-18; 4:25-26) -- To run in vain (Gal 2:2) -- Nationalism and church policy: reflections on Galatians 2:9 -- Galatians 2:15-16a: whose common ground? -- The irrevocable will (Gal 3:15) -- Galatians 4:13-14 and the recipients of Galatians -- The unwritten law of Christ (Gal 6:2) -- The origins of Paul's Christology: from Thessalonians to Galatians
Includes bibliographical references (p. 175-185) and indexes
Keywords: Paulus -- Apostel, Heiliger; Bible -- Criticism, interpretation, etc -- Bible -- Criticism, interpretation, etc; Bibel; Bibel; Aufsatzsammlung; Biografie; Christologie; Soteriologie; Rechtfertigung; Gesetz; Judenchrist; Mission; Urchristentum; Urchristentum; Messias; Messianismus